A study on overall services of System Solutions and Development Technologies Limited (SSD-Tech) - Hossain, Md. Istiyak (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.